سيميائية العتبات النصية في الرواية النسوية العربية روايتي بغداد و قد انتصف الليل فيها لحياة الرايس و كذبة إبريل لسمر المقرن أنموذجا - ميلودي, بوعلاق, رشيدة يونس (Univercty of Eloued, 2020)
سيميائية العتبات النصية في الرواية النسوية العربية روايتي (بغداد وقد انتصف الليل فيها لحياة الاريس، وكذبة إبريل لسمر المقرن ) ً أنموذجا سعيت من خلال هذه الدارسة للكشف عن تجليات العتبات النصية الداخلية والخارجية في الرواية النسوية العربية للكتابة النسوية في المشرق العربي ً من خلال روايتين كأنموذجا ومغربه، ومن أجل ذلك جاءت دارستي وفق الخطة التالية: الفصل الْول :تناولنا فيه مفاهيم لكل من السيميائية والعتبات النصية والرواية النسوية . وقضايا الكتابة النسوية ، وا شكالية مصطلح العتبات النصية وتمظهارتها عند العرب والغرب الفصل الثاني :دارسة العتبات النصية في الروايتين من عتبات خارجية (العنوان، الصورة المصاحبة "الشكل واللون"، اسم المؤلف )وعتبات داخلية (الْهداء، الاستهلال، المقدمة، العناوين الداخلية)، ومزجنا بين النظري والتطبيقي، لنصل في الختام إلى أهمية العتبات النصية في خدمة الخطاب الروائي وخاصة الرواية النسوية العربية. The semiotics of textual thresholds in the Arab feminist novel, my novel (bagdad w kad intasafa elail fiha "HAYET ERRAIES"- kidbat ipril "SAMAR ELMOGREN"( A model Through this study, I sought to reveal the manifestations of the internal and external textual thresholds in the Arab feminist novel through two novels as a model for feminist writing in the Arab East and West, and for that my study came according to the following plan: The first chapter: We dealt with concepts of semiotics, textual thresholds, feminist narration, the problem of the term textual thresholds and their manifestations among Arabs and the West, and issues of feminist writing. Chapter Two: Study the textual thresholds in the two novels from external thresholds (the title, accompanying picture "shape and color", the author's name) and internal thresholds (dedication, introduction, introduction, and internal titles), and we combined the theoretical and practical, so that in conclusion we arrive at the importance of textual thresholds in Narrative discourse service, especially the Arab feminist novel.
Keywords: العتبات الداخلية والخارجية العتبات النصية النص المناص الرواية النسوية; textual thresholds - text - transcripts - headline - internal and external thresholds - the feminist narrative.